Pengaruh Luas Lahan dan Jumlah Produksi Kelapa Sawit terhadap Produk Domestik Regional Bruto (PDRB) Sub. Sektor Perkebunan di Propinsi Bengkulu Tahun 2011-2021 - Williadi; As’ad; Teguh Dwi Arsyah (Economic Reviews Journal, 2024)
Agriculture has an important role for the economy in Indonesia. One of the agricultural sub-sectors is plantations, the role of agriculture is proven by its effect on GRDP. GRDP is a determinant of measuring regional economic development. This research aims to find out how and how much influence the land area and amount of palm oil production have on the GRDP of the Plantation Sub-Sector in Bengkulu Province. This research uses secondary data obtained from the official website of the Central Statistics Agency, totaling 11 samples. The results of the multiple linear regression test show that there is a positive and significant relationship between land area and total palm oil production on GRDP in the Plantation Sub-Sector in Bengkulu Province, both partially and simultaneously.The contribution of land area and total production to GRDP in the agricultural sub-sector was 45.5% in Bengkulu Province during 2011-2021.